Ecological Strategy to Prevent Vulture Menace to Aircraft in India - Singh, R.B. (Defence Science Journal, 2013)
Vultures are sincere scavengers. Though seen with disgust, they work silently as effective biological incinerators of nature by feeding and digesting the diseased and rotten animal carcasses. Vultures are shifting their natural habitat and proliferating unnaturally in the cities because of encroachment of forest, unplanned industrialisation, urbanisation, and uncivilised way of life prevailing in the society. Hence, the problem of vulture menace to aircraft has arisen. Vulture strikes to aircraft can be minimised by promptly lifting the dead animals/carcasses from different parts of the city to the permanent feeding ground, which should be out of buffer zone area and away from the flying path. and simultaneously discouraging the illegal skinning, specially in the vicinity of aerodrome. In this paper, an ecological solution of the vulture strike to aircraft is highlighted.